Investigating the Impacts of Mergers and Acquisitions on Firm’s Operating Performance: Evidence from Chinese Acquiring Companies - ZHU, LIN (2016)
Mergers and acquisitions (M&A) are considered to be one of most widely used investments by companies to improve financial and operating performance. Nevertheless, although there are extensive literature focusing on M&A markets in the developed countries, empirical studies based on the Chinese M&A market are quite limited. This dissertation attempts to provide new evidence for existing literature on M&A by investigating the relationship between M&A and acquirers’ operating performance and examining explanatory role of M&A deal-specific characteristics on post-merger operating performance for the sample of 155 domestic transactions undertaken between January 1, 2003 and December 31, 2012. The conclusion can be drawn that acquirers’ operating performance, measured by operating cash flow return on total assets, return on assets, inventory turnover and sales growth, are consistently deteriorated following M&A estimated by the change model, while the results of intercept model report significant improvements or no change in post-merger operating performance. Additionally, cross-sectional regression shows that bidding firms’ operating performance are significantly improved following M&A when transactions occur between firms belong to the related industry or during the period of financial crisis. Apart from that, the deal size is also considered to be significantly related with bidders’ operating performance, while relative size of target and acquirer cannot explain post-merger operating performance. Furthermore, the previous conclusion is still valid for the robustness test.